Dietary patterns and the risk of non-Hodgkin lymphoma. Issue 7 (9th May 2013) - Ollberding, Nicholas J; Aschebrook-Kilfoy, Briseis; Caces, Donne Bennett D; Smith, Sonali M; Weisenburger, Dennis D; Chiu, Brian C-H
Abstract Objective Previous studies examining the role of single foods or nutrients in the aetiology of non-Hodgkin lymphoma (NHL) have produced inconsistent findings. Few studies have examined associations for dietary patterns, which may more accurately reflect patterns of consumption and the complexity of dietary intake. The objective of the present study was to examine whether dietary patterns identified by factor analysis were associated with NHL risk. Design Case–control. Setting Population-based sample residing in Nebraska from 1999 to 2002. Subjects A total of 336 cases and 460 controls. Results Factor analysis identified two major dietary patterns: (i) a 'Meat, Fat and Sweets' dietary pattern characterized by high intakes of French fries, red meat, processed meat, pizza, salty snacks, sweets and desserts, and sweetened beverages; and (ii) a 'Fruit, Vegetables and Starch' dietary pattern characterized by high intakes of vegetables, fruit, fish, and cereals and starches. In multivariable logistic regression models, the 'Meat, Fat and Sweets' dietary pattern was associated with an increased risk of overall NHL (ORQ4v.Q1 = 3·6, 95 % CI 1·9, 6·8; Ptrend = 0·0004), follicular lymphoma (ORQ4v.Q1 = 3·1, 95 % CI 1·2, 8·0; Ptrend = 0·01), diffuse large B-cell lymphoma (ORQ4v.Q1 = 3·2, 95 % CI 1·1, 9·0; Ptrend = 0·09) and marginal zone lymphoma (ORQ4v.Q1 = 8·2, 95 % CI 1·3, 51·2; Ptrend = 0·05). No association with overall or subtype-specific risk was detected for the 'Fruit, Vegetables and Starch' dietary pattern. No evidence of heterogeneity was detected across strata of age, sex, BMI, smoking status or alcohol consumption. Conclusions Our results suggest that a dietary pattern high in meats, fats and sweets may be associated with an increased risk of NHL.